Environmental knowledge level in undergraduate students: University of San Pedro, Peru - TauccayaI, Oscar Julián Berrios; Reyes, David Ricse; More, Leandro Vallejos; Mendoza, Prospero Cristhian Onofre Zapata (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Studies specifically referring to the evaluation of learning levels and awareness of university students in environmental matters are incipient. In that order, the objective of this research is to establish the influence curriculum of the San Pedro University, Sullana subsidiary on the level of environmental knowledge of undergraduate students, 2017. The research design is non-experimental, applicative, observational and descriptive. The study population corresponds to undergraduate students of the San Pedro University, Sullana, 2018. The total population comprises 2050 students; the sample is structured by a non-probabilistic sample, represented by 188 undergraduate students of the San Pedro University Sullana 2017, students from different Professional Schools. The survey technique was applied, through a knowledge assessment questionnaire on environmental issues. With a significance level of 0.05, it was demonstrated that the Study Plan of the San Pedro University subsidiary Sullana 2017 doesn’t have any significant influence on the level of environmental knowledge of undergraduate students. With an average of 2.73% of the courses dedicated to the environmental issue, it is concluded that environmental issues are not a priority within the curricular contents of the San Pedro University, Sullana subsidiary.